63.7k views
24 votes
Solve using the elimination method.
2x-3y=7
4x-4y=4

2 Answers

11 votes

Explanation:

2x-3y=7-----------(1)

multiply by 2 in first equation

4x-6y=14------------ (2)

4x-4y=4---------------(3)

then, subtracting eqn (3) from (1)

4x-6y=14

4x-4y=4

sin change - + -

_________

-2x=10

x=-5

putting value of x on eqn (3)

4x-4y=4

-20-4y=4

-4y=24

y=-6

User Stephani Bishop
by
5.5k points
6 votes

Answer:

x=4, y=5

Explanation:

You obtain an answer by subtracting the second equation from the first.

User Zanga
by
6.2k points